Factors Influencing Preventive Behaviors for Cerebrovascular Disease among Elderly Risk Group of Tertiary Hospital - Robrujen, Suwimolrat; Nganchaturas, Sopapan; Thongkwan, Watcharapon; Somhom, Wanpen; Khunkhavan, Torranin; Lalun, Ananya; Vutiso, Pitoon (Journal of The Royal Thai Army Nurses, 2023)
This research aimed to; 1) Behaviors for cerebrovascular disease among elderly risk group of tertiary hospital 2) study factors Influencing preventive behaviors for cerebrovascular disease among elderly risk group of tertiary hospital The sample consisted of 136 among elderly risk group of tertiary hospital. The research instrument was a questionnaire composed of 5 parts: demographic data, stroke knowledge, risk perception factors, severity of stroke, perceived benefits and obstacles to stroke prevention practices, social support and stroke preventive behaviors. The content validity index of a questionnaire was 0.88 and Knowledge questionnaire finds KR - 20 equal to 0.82, the reliability coefficients of each sub-parts, were 0.84, 0.81, 0.86 and 0.86 respectively. Descriptive statistics and Stepwise multiple regression analysis were used in data analysis. Statistical significance was set at the level of .05 The results were as follows. among elderly risk group of tertiary hospital, knowledge of cerebrovascular disease was at the high level with 43.4 percent. risk perception factors showed the moderate level of 71.3 percent. severity of stroke factors showed the high level of 86.1 percent. perceived benefits factors showed the moderate level of 52.2 percent. and obstacles to stroke prevention practices factors showed the moderate level of 45.6 percent. Social Support communication factors showed the moderate level of 54.4 percent , family factors showed the moderate level of 69.1 percent, neighbor factors showed the moderate level of 63.2 percent, staff personnel factors showed the high level of 56.6 percent and preventive behaviors for cerebrovascular disease showed the moderate level of 89.7 percent. Factors associated with perceived severity of disease (B = 0.080) and social-emotional and family support (B = 0.109) can jointly predict stroke prevention behaviors in the elderly, at risk groups, tertiary care hospitals in overall 8.8 percent of the variance of stroke preventive behavior at p <.05.